Activation and Biological Properties of Human β Defensin 4 in Stem Cells Derived From Human Exfoliated Deciduous Teeth - Zhai, Yue; Wang, Yuanyuan; Rao, Nanquan; Li, Jingzhi; Li, Xiaoxia; Fang, Tengjiaozi; Zhao, Yuming; Ge, Lihong (Frontiers in Physiology, 2019)
Pulpitis in primary teeth, a condition caused by presence of bacteria, is highly prevalent worldwide. The use of biocompatibility materials with anti-inflammatory, anti-bacterial, and regenerative properties is critical for prognosis of this endodontic disease. This study aimed to identify expression of human β defensin 4 (HBD4) in stem cells derived from human exfoliated deciduous teeth (SHED) and characterize the effects of HBD4 on SHED. Quantitative polymerase chain reaction (qPCR) was used to detect HBD4 expression in SHED and the effect of HBD4 on inflammatory factors in lipopolysaccharide (LPS)-stimulated SHED. Affinity measurement was made by the Fortebio Octet System to explore the potential interaction between LPS and HBD4. Western blot analysis was used to explore the effect of HBD4 on mitogen-activated protein kinase (MAPK) pathway. Colony-forming unit methods and scanning electron microscopy were applied to study antimicrobial effect of HBD4 on Fusobacterium nucleatum and Porphyromonas gingivalis. Alkaline phosphatase staining, alizarin red staining, qPCR and western blot were taken to detect effects of HBD4 on osteoblast/odontoblast differentiation of SHED. RT2 Profiler PCR Array was used to explore the potential signaling pathways involved in the osteogenic/odontogenic differentiation. HBD4 was highly expressed in SHED stimulated by TNF-α and IL-1α. HBD4 could bind to LPS directly and down-regulate IL-1α, IL-1β, IL-6, TNF-α in LPS-stimulated SHED, thus the activation of MAPK pathway decreased. HBD4 was sensitive to P. gingivalis and enhanced osteoblast/odontoblast differentiation potential of SHED by modulating Notch pathway. HBD4 was highly expressed in SHED stimulated by proinflammatory cytokines, and possessed anti-inflammatory, anti-bacterial activity. HBD4 promoted osteogenic/odontogenic differentiation of SHED. HBD4 may thus represent a suitable agent for vital pulp therapy in future clinic application.